2015
DOI: 10.1098/rsbl.2015.0558
|View full text |Cite
|
Sign up to set email alerts
|

Contests with deadly weapons: telson sparring in mantis shrimp (Stomatopoda)

Abstract: Mantis shrimp strike with extreme impact forces that are deadly to prey. They also strike conspecifics during territorial contests, yet theoretical and empirical findings in aggressive behaviour research suggest competitors should resolve conflicts using signals before escalating to dangerous combat. We tested how Neogonodactylus bredini uses two ritualized behaviours to resolve size-matched contests: meral spread visual displays and telson (tailplate) strikes. We predicted that (i) most contests would be reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…As we could not record resident behaviours inside the burrow, we were unable to quantify this behaviour. However, we did observe punches onto the opponent's telson, as described by Green & Patek [47]. It is possible that residents also increased the frequency of offensive behaviours in the UV reduction treatment group, in response to intruders performing more aggressive behaviours.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As we could not record resident behaviours inside the burrow, we were unable to quantify this behaviour. However, we did observe punches onto the opponent's telson, as described by Green & Patek [47]. It is possible that residents also increased the frequency of offensive behaviours in the UV reduction treatment group, in response to intruders performing more aggressive behaviours.…”
Section: Discussionsupporting
confidence: 68%
“…This was as expected because we altered only the resident's signal, not its fighting ability. However, recent research in N. bredini has demonstrated that whichever stomatopod punches their opponent's telson more times (a behaviour known as telson sparring ) is the stomatopod more likely to win the contest [47]. As we could not record resident behaviours inside the burrow, we were unable to quantify this behaviour.…”
Section: Discussionmentioning
confidence: 95%
“…Further studies, including the assessment of the risks of striking and the energetics of strikes, will be required to test how mantis shrimp strategically use their lethal weapons safely and effectively (e.g. Green and Patek, 2015). Preparatory control of kinematics raises key questions for future research about the underlying trigger mechanism and the ability to predict the kinematics needed across a range of behavioral and biomechanical contexts.…”
Section: Broader Implications For Behavioral and Neural Controlmentioning
confidence: 99%
“…In conclusion, mantis shrimp can control spring compression and strike velocity in advance of a strike, thus conferring potential damage resistance due to overuse of the hammer, energy savings by using appropriate kinematics for different targets, and the ability to perform strategic kinematics for the various uses of the hammers, such as ritualistic fighting, modifying home sites, knocking out prey, fracturing hardshelled prey and puncturing evasive prey (Adams and Caldwell, 1990;Caldwell and Dingle, 1975;Full et al, 1989;Green and Patek, 2015). Further studies, including the assessment of the risks of striking and the energetics of strikes, will be required to test how mantis shrimp strategically use their lethal weapons safely and effectively (e.g.…”
Section: Broader Implications For Behavioral and Neural Controlmentioning
confidence: 99%
“…As well as signals that are attuned to the psychology of receivers (sensu [38]), accuracy could encompass the delivery of strikes if the opponent must be struck on a specific body part (e.g. on the telson in fighting mantis shrimp [39]). In addition to accuracy, precision may also be important if victory depends on the consistency of agonistic behaviour within a fight, for example, repeatedly striking the same area of the opponent within narrow parameters of variation.…”
Section: Skilful Fightingmentioning
confidence: 99%